(untitled) (Global Journal of Medical Research, 2017)
Blighia sapida is a plant belonging to the family of sapindaceae. In this study we aimed to evaluate the in vivo antioxidant activities of aqueous extract of Blighia sapida stem bark in alloxan-induced diabetic rats. Administration of the extract at 100mg/kg body weight significantly (P